Relationship Between Teachers’ Motivation, Attitude and Students’ Academic Achievement in Senior Secondary Schools in Bauchi Metropolis - Bada, S. Olusegun; Ibrahim, M. Inuwa; Aliyu, A. Umar; Sani , Abubakar (Kashere Journal of Education, 2022)
This study investigated the influence of teachers' motivation and teachers’ attitudes, on students’ academic achievement in secondary schools in Bauchi metropolis in Bauchi state, Nigeria. Correlational research design was used. Teachers’ Motivation Questionnaire (TMQ), and Teachers’ Attitude Questionnaire (TAQ) were adapted and used for the research study. Three hypotheses were tested at 0.05 level of significance. The statistical tools used were Multiple Regression Analysis and Pearson's Product Moment correlation coefficient. The participants in this study were made up of 191 teachers and purposively selected from the population of 382 teachers of English and Civic Education across 26 senior secondary schools in Bauchi metropolis. Multiple regression analysis discovered that there is a significant positive relationship among teachers' motivation, teachers' attitudes and students’ academic achievement (f= +13061, p<0.05), and also shows that 12 percent of variance in student achievement is contributed by teachers' motivation and teacher attitudes scores (R2= +0.122). The results further revealed a significant relationship between the motivation of teachers and students’ academic achievement (r= +0.304, p<0.05), and there is significant relationship between teachers' attitudes and students’ academic achievement (r= +0.243, p<0.05). The study recommends among others that, teachers should be motivated by government and education stakeholders in order to improve teachers’ attitudes toward teaching and students’ academic achievement.